Corporate Culture in Mining Industry: A Comprehensive Literature Review on Development and Integration - Kusnadi, Iyas; Gustomo, Aurik; Airef, N. Nurlaela (International Journal of Social Science and Business, 2024)
This literature review examines how corporate culture development and integration in the mining industry affect employee management, including relations, engagement, and development. The aim is to analyze existing research to understand the significance and impact of corporate culture on employees within this sector. The review involved shortlisting 600 journals and analyzing 42 articles using a systematic critical review, complemented by a meta-analysis through VOS Viewer software. A taxonomy of the research gap was applied to identify areas for further exploration. The findings highlight the critical role of leadership in shaping and promoting corporate culture, as well as the strategies and approaches required for successful culture development initiatives in the mining industry. The meta-analysis from VOS Viewer suggests the need for further investigation into this area, while the systematic review uncovers gaps related to population, evidence, and knowledge. The study acknowledges limitations in the existing literature, recommending future research to address these gaps and enhance the understanding of effective corporate culture practices. The originality of this review lies in its methods, offering valuable insights for both practitioners and scholars interested in fostering corporate culture development and integration, contributing to the advancement of knowledge in the field.